Glocal Religions - Victor Roudometof (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
ca. 200 words; this text will present the book in all promotional forms (e.g. flyers). Please describe the book in straightforward and consumer-friendly terms. [enter Summary/Description] The globalization of the world's religions leads to a variety of fusions whereby local elements blend with global religions, leading to hybrid local-global or glocal religious forms. Glocal forms of religion provide a hitherto insufficiently explored research agenda with the potential of further growth in the future. This volume introduces the basic tenets of this research agenda and offers examples from around the globe. In the volume's individual chapters, authors explore a diverse tapestry of such forms that cover cases from the Caribbean, Japan, Finland, Eastern Europe, US, Korea, Southeast Asia and Central America. Glocal forms of religious expression exist across diverse religious traditions. In this volume, religious traditions specifically explored include Buddhism, Hinduism, folk or traditional religions, Eastern Orthodox Christianity & Protestantism. The study of glocal religions involves a trans-disciplinary group of scholars and researchers. In this volume, contributions come from the fields of sociology, archaeology, anthropology, history and religious studies. This collection is an indispensable reader for scholars and students who wish to explore the dynamics of glocal religion in their part of the world.